Coronavirus: Winning the battle against the epidemic will depend on health education and the social responsibility of citizens - Ubillús, Milward (2020)
As expected, sooner rather than later, the COVID-19 pandemic arrived in Huánuco and, as in every community, has caused collective hysteria, expressed in the fear and desperation of coming face to face with death. In spite of the desperate actions and dispositions dictated by a government whose health sector has proven experience in previous epidemics from which it came out well; such as the cholera that, in 1991, claimed 323,000 affected people and 2,900 deaths, much less than in other countries.